Features of premorbid behavioral patterns of binge eating in favor of binge eating disorder as a targeted personalized intervention - Сінькевич, Інна; Хаустова, Олена (Psychosomatic Medicine and General Practice, 2024)
Relevance. Overeating is a key feature of eating behavior disorders such as bulimia nervosa, anorexia nervosa, and binge eating disorder (BED). Binge eating disorder was first included as a research diagnosis in DSM-IV and later recognized as an official diagnosis in DSM-5. It is also included in the ICD-11. Overeating is associated with significant mental and physical health problems, including depression, anxiety, substance abuse, and chronic somatic diseases. Objective. The aim of the study was to assess the premorbid psychosocial patterns of overeating in patients with binge eating disorder (BED) in order to identify potential targets for personalized medical-psychological intervention. Methods and Materials. An open cohort study was conducted among 163 patients with BED. After obtaining informed consent from the participants, body mass index (BMI) and the Symptom Index of the Eating Disorder Inventory were used to verify the overeating pattern. The patients were grouped according to the type of overeating: emotional, compulsive, and situational. Emotional overeating is associated with negative emotions, compulsive overeating with uncontrollable urges to eat, and situational overeating with external circumstances. For the diagnosis of overeating disorder, the regularity of overeating episodes is important, which should occur at least once a week. Results. The average age of the patients was 34.6 ± 11.7 years, with the majority being women (60.12%). The BMI exceeded healthy levels in nearly 80% of participants. The most common type of overeating was emotional (73.01%), followed by situational overeating (46.63%). The severity of overeating ranged from mild (23.93%) to very severe (4.29%). Men had a statistically higher incidence of compulsive overeating (p < 0.026) and a greater number of coexisting overeating types. The study showed that premorbid overeating patterns persisted even during periods of remission in BED. In patients with mild and moderate severity of overeating, the emotional type predominated, which in more severe cases was combined with situational overeating. Men typically had more severe forms of BED, with compulsive overeating being more characteristic of men (p < 0.026). It was also found that patients with very severe BED more frequently exhibited combinations of emotional and situational overeating. Conclusions. The results of this study provide insights into premorbid overeating patterns as an important component of medical-psychological intervention in the treatment of BED. This allows for the development of more effective and personalized therapeutic strategies for patients with different types and severities of the disorder.